If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(3b+4)=3(2b+2)
We move all terms to the left:
3(3b+4)-(3(2b+2))=0
We multiply parentheses
9b-(3(2b+2))+12=0
We calculate terms in parentheses: -(3(2b+2)), so:We get rid of parentheses
3(2b+2)
We multiply parentheses
6b+6
Back to the equation:
-(6b+6)
9b-6b-6+12=0
We add all the numbers together, and all the variables
3b+6=0
We move all terms containing b to the left, all other terms to the right
3b=-6
b=-6/3
b=-2
| 15x+3=63 | | H(t)=-16t^2+48t+32 | | 90/x=0.6 | | -3/4=-1/6t | | 3x8=2 | | 1/2x-5=3/4x-8 | | 2x+9+3x=29 | | 3x-4/18+x=3x+4/3+2 | | 6(8x-2)=8(6x-8) | | (8/9)(3x-1)/(2)-(2/3)(3x+5)=2x+7 | | (8)/(9)(3x-(1)/(2))-(2)/(3)(3x+5)=2x+7 | | 4(2x-3)=3+5x-11+3x | | 4(-2x+1)=6-(8x-7) | | (1+r)^5=1.6105 | | 2(x+1)+3x=3x | | 0.8888888889(3x-0,5)-0.6666666667(3x+5)=2x+7 | | 10/4x+1=100 | | x+4/7x=77 | | 8/9(3x-0,5)-2/3(3x+5)=2x+7 | | 9x+11=-7x+1+2x | | (X-4)/4=(x+4)/7 | | x^2=-8x-8 | | 8n+18n÷6=0 | | 9t=144 | | 3x+1/3x=50 | | 6(n−1)+2=n(4+2)+4 | | 11/12=12/p | | 0,25(x+13)=1,5x+7 | | (1+4x)(3x^2-2x)+(x-3)=0 | | 1/4(x+13)=3/2x+7 | | 3.5x+42=45 | | (7x-4)(8x+1)=0 |